STRATEGI PENGEMBANGAN DAYA TARIK WISATA RUMAH TRADISIONAL MASYARAKAT KAMPUNG LOLOAN, JEMBRANA-BALI - Pramesti, Dinar Sukma (TOURISM: Jurnal Travel, Hospitality, Culture, Destination, and MICE, 2019)
This research aimed at analyzing the development strategies of Loloan traditional houses to become a tourist attraction which is beneficial for the local community. This study is a descriptive qualitative study using a SWOT analysis. The informants were chosen based on purposive sampling. Based on SWOT analysis, some strategies can be implemented in Loloan Village. Those are the development of homestay, tour package, establishment of organization to manage the tourism potential, the implementation of community based tourism, the empowerment of local community by developing their awareness on tourism, the improvement of marketing strategy, make some stilt housing units as cultural assets owned by the government and being the piloting project, the development of tourism activities, and the improvement of its facilities.